Combined additive manufacturing process for the production of sustainable concrete modules for the construction of a tiny house - Abstoß Marvin; Funke Henrik; Gelbrich Sandra (MATEC Web of Conferences, 2025)
The work is about the development of a clinker-reduced concrete with a maximum grain size of 5.6 mm. The concrete is processed into modules for the construction of a tiny house using additive manufacturing technologies such as 3D printing and spraying. The influence of various production parameters on the result was analysed. A 3D scan of the surfaces produced made it possible to assess the geometric dimensions of the components as well as a target/actual comparison through parametric programming using Grasshopper, an add-on for the CAD programme Rhinoceros 3D. Furthermore, the milling of the material was analysed and used as an option to create precise module edges. Subsequently, a mineral-based, lightly bonded material was developed on the basis of lightweight fillers, which enables the automated insulation of the modules within the manufacturing process. The parametric programming of the modules enables the creation of a digital twin. Life cycle management can be implemented using the digital twin. This means that individual modules can continue to be used after the tiny house has been disassembled.